24‐1: Invited Paper: Optically Invisible Antenna‐on‐Display (AoD) Technologies: Review, Demonstration and Opportunities for Microwave, Millimeter‐Wave and Sub‐THz Wireless Applications. Issue 1 (28th June 2021) - Park, Junho; Kim, Bumhyun; Hong, Wonbin
Abstract : This paper provides a detailed overview of an optically invisible phased‐array antenna‐on‐display (AoD) technology for microwave, millimeter‐wave (mmWave), and sub‐THz wireless scenarios such as wireless communication, radar, sensing etc. The fundamental AoD configuration and stack‐up are introduced with numerical results, which proves the trade‐off relationship between optical transmittance and RF conductivity. A transverse magnetic patch antenna for Wi‐Fi and Bluetooth accessibility is implemented on the active display panel of a real‐life smartwatch device. The fully functional smartwatch prototype including the electromagnetic wrist phantom features a total radiation efficiency of 22% at 2.4 GHz. The optically invisible phased‐array AoD is fully integrated within the view area of high‐resolution OLED display panels of mmWave 5G NR cellular handsets. The fabricated cellular handset prototype including optically invisible beamforming AoD features optical transmittance of more than 88 % and beam scanning of ± 30° with the estimated maximum EIRP of 14.4 dBm. The over‐the‐air test confirms that the fabricated phased‐array AoD prototype satisfies the 3GPP's EVM performance requirement for 5G NR cellular devices. Future work collectively aims to serve as a catalyst for the emergence of future sub‐THz 6G mobile devices.